2018
DOI: 10.3390/magnetochemistry4040044
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Circle of the Lanthanide-Murexide Series: Single-Molecule Magnet Behavior and Near-Infrared Emission of the NdIII Derivative

Abstract: Up to now, even if murexide-based complexometric studies are performed with all 3d or 4f ions, the crystal structures of the light-lanthanide derivatives of the lanthanide-murexide series are unknown. In this work, we report the crystal structure of the NdIII derivative named NdMurex. Contrary to all known complexes of the 3d or 4f series, a dimeric compound was obtained. As for its already reported DyIII and YbIII parents, the NdIII complex responsible for the color-change behaves as a single-molecule magnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 72 publications
0
21
0
1
Order By: Relevance
“…This makes it more difficult to achieve slow magnetic relaxation in complexes based on such ions. Although their NIR luminescence has been extensively studied in the context of the production of lasers and Ln 3+ ‐doped glasses, no reports have yet been made on the combination of luminescent and magnetic properties in a complex based on Ho 3+ , while only one weakly emitting Nd 3+ SMM has been reported under direct excitation of the Ln 3+ centre [120a] . Tm 3+ is an even less explored choice for the preparation of (luminescent) SMMs.…”
Section: Luminescent Smmsmentioning
confidence: 99%
“…This makes it more difficult to achieve slow magnetic relaxation in complexes based on such ions. Although their NIR luminescence has been extensively studied in the context of the production of lasers and Ln 3+ ‐doped glasses, no reports have yet been made on the combination of luminescent and magnetic properties in a complex based on Ho 3+ , while only one weakly emitting Nd 3+ SMM has been reported under direct excitation of the Ln 3+ centre [120a] . Tm 3+ is an even less explored choice for the preparation of (luminescent) SMMs.…”
Section: Luminescent Smmsmentioning
confidence: 99%
“…Among the mononuclear Nd-SMMs, the coordination numbers of Nd III cations are mostly seven, eight, nine and twelve. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]62 Although the seven-coordinate Nd III compounds exhibit better SMM behavior possibly due to the high symmetry of configuration, the effective energy barriers are lower. [52][53][54] In comparison, eight-coordinate Nd III compounds present fieldinduced slow magnetic relaxation behavior with higher energy barriers.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…31 Very recently, our group obtained a novel μ 3 -O-capped {Er 3 } cluster containing the POM K 20 O, which displays field-induced SMM behavior with two magnetic relaxation processes. 34 In particular, Nd-based SMMs are relatively less studied, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] with only two successful examples of Nd-POM SMMs having being reported to date. 62,63 In detail, Baldoví et al reported the first example of the structure of the Nd-POM singleion magnet [Nd(W 5 O 18 ) 2 ] 9− with an effective barrier of 51.4 cm −1 under an applied field in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Diese macht es schwieriger, bei auf solchen Ionen beruhenden Komplexen eine langsame magnetische Relaxation zu erreichen. Obwohl ihre NIR‐Lumineszenz im Zusammenhang mit der Herstellung von Ln 3+ ‐dotiertem Laserglas intensiv erforscht wird, gibt es noch keine Veröffentlichungen über die Kombination lumineszierender und magnetischer Eigenschaften bei einem Ho 3+ ‐Komplex, während nur ein schwach emittierender Nd 3+ ‐SMM unter direkter Anregung beschrieben wurde [120a] . Tm 3+ ist eine noch weniger erforschte Alternative für die Herstellung von (lumineszierenden) SMMs.…”
Section: Lumineszierende Smmsunclassified